Effect of ion chelator on microstructure and properties of cement-based materials under sulfate dry-wet cycle attack. (10th October 2020) - He, Peng; Yu, Jianying; Wan, Yang; Wang, Ruiyang; Han, Xiaobin; Gu, Shunjie; Liu, Quantao
Highlights: Ion chelator improves the pore structure of mortar under sulfate dry-wet attack. Sulfate corrosion resistance of mortar has been enhanced by ion chelator. The impermeability and mechanical strength of mortar is improved by ion chelator. Abstract: Ion chelator can promote the self-healing process of cement-based materials. The aim of present study is to investigate the effect of ion chelator on microstructure and properties of cement-based materials under sulfate dry-wet cycle attack. The micromorphology and pore structure of mortar were characterized by scanning electron microscope (SEM) and nuclear magnetic resonance (NMR). The impermeability of mortar was evaluated by chloride diffusion coefficient. Meanwhile, mass loss, mechanical strength, and corrosion resistance coefficient (K) of mortar were measured. The results showed that ion chelator could improve microstructure and mechanical properties of cement-based materials by enhancing their self-healing ability. After 60 cycles of sulfate dry-wet, SEM showed that there was a large degree of erosion formed on the surface of control mortar (CM), while slight erosion occurred on the surface of mortar with ion chelator (MCA). NMR indicated that the proportion of harmful pores (≥0.1 μm) in CM and MCA was 50.19% and 42.86%, especially, the proportion of harmful pores from 0.25 μm to 25.0 μm in mortar is obviously reduced with the addition of ion chelator. And the compressive strength of MCA was 33.6% higher than that of CM, and the chloride diffusion coefficient of MCA was 25% lower than that of CM. Meanwhile, the mass loss ratios of CM and MCA were 1.78% and 0.91% and the K values of CM and MCA were 0.79 and 0.92 respectively. Conclusion can be drawn that ion chelator significantly improves the microstructure and properties of cement-based materials under sulfate dry-wet cycle attack.